Monitoring prolongation of QT interval in patients with multidrug-resistant tuberculosis and non-tuberculous mycobacterium using mobile health device AliveCor. (February 2022) - Puranik, Shriya; Harlow, Christopher; Martin, Laura; Coleman, Meg; Russell, Georgina; Park, Mirae; Min Kon, Onn
Abstract: Multidrug resistant tuberculosis and non-tuberculous mycobacterium infections present challenges due to complex treatment regimens. Extended treatment regimes expose patients to higher risks of toxic side-effects. A high drug toxicity profile necessitates closer monitoring. One of the more challenging issues is QTc prolongation with non-injectable regimens. This study investigates the portable AliveCor device to record and measure the QTc on a 6-lead ECG. An automated QTc readout from 12-Lead ECG for each patient (n = 13) and mean QTc value calculated from each patients' respective AliveCor tracing were compared. The general trend suggests AliveCor underestimates QTc − 92% cases calculated the AliveCor QTc as lower than their corresponding 12-Lead QTc readout. The use of AliveCor could potentially be translated into current clinical practice with caution of percentage variation either side. This could facilitate the use of AliveCor as a promising and convenient screening tool before further evaluation by a 12-Lead ECG is required.